2012
DOI: 10.1148/radiol.12120041
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of MR Imaging in the Evaluation of Clinically Low-Risk Prostate Cancer: A Prospective Study

Abstract: Dr(hc) Purpose:To prospectively evaluate diagnostic performance of T2-weighted magnetic resonance (MR) imaging and MR spectroscopic imaging in detecting lesions stratified by pathologic volume and Gleason score in men with clinically determined low-risk prostate cancer. Materials and Methods:The institutional review board approved this prospective, HIPAA-compliant study. Written informed consent was obtained from 183 men with clinically low-risk prostate cancer (cT1-cT2a, Gleason score  6 at biopsy, prostates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 42 publications
4
39
1
Order By: Relevance
“…Also, the inability of current imaging tools to provide an accurate assessment of prostate cancer volume has contributed to the difficulty of reliably identifying insignificant prostate cancers. 13,14 Since the original definition of pathologically insignificant prostate cancer was proposed more than 15 years ago, prostate cancer diagnostics have evolved. A stage and grade migration of detected prostate cancers has occurred [15][16][17] and pathologists have modified the criteria for Gleason grading, particularly with respect to grading prostate needle biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the inability of current imaging tools to provide an accurate assessment of prostate cancer volume has contributed to the difficulty of reliably identifying insignificant prostate cancers. 13,14 Since the original definition of pathologically insignificant prostate cancer was proposed more than 15 years ago, prostate cancer diagnostics have evolved. A stage and grade migration of detected prostate cancers has occurred [15][16][17] and pathologists have modified the criteria for Gleason grading, particularly with respect to grading prostate needle biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Vargas et al [16] reported that the detection of lesions less than 1 cm 3 with T2-WI was significantly dependent on their GS. They further noted that the detection of lesions greater than or equal to 1 cm 3 was significantly better than the detection of smaller lesions, and is not affected by the lesion's GS, demonstrating that the tumor volume affects detectability on T2-WI.…”
Section: Discussionmentioning
confidence: 99%
“…This is true in particular for anterior and apical prostate cancers [38]. Prostate cancers with a volume of > 0.5 cm³ are detected with the help of MRI with a diagnostic accuracy of 0.91 to 0.94 [39]. If the Gleason score is taken into consideration in this analysis, the sensitivity for the detection Fig.…”
Section: Computer-assisted Ultrasoundmentioning
confidence: 98%